2015
DOI: 10.14348/molcells.2015.0094
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid (UDCA) Exerts Anti-Atherogenic Effects by Inhibiting Endoplasmic Reticulum (ER) Stress Induced by Disturbed Flow

Abstract: Disturbed blood flow with low-oscillatory shear stress (OSS) is a predominant atherogenic factor leading to dysfunctional endothelial cells (ECs). Recently, it was found that disturbed flow can directly induce endoplasmic reticulum (ER) stress in ECs, thereby playing a critical role in the development and progression of atherosclerosis. Ursodeoxycholic acid (UDCA), a naturally occurring bile acid, has long been used to treat chronic cholestatic liver disease and is known to alleviate endoplasmic reticulum (ER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…ER stress and the UPR in ECs can be mediated through the mechanosensitive pathway. Disturbed flow and low magnitude shear stress act through ER stress to promote vascular cell adhesion molecule 1 expression and monocyte adhesion to the endothelium, early events in atherosclerosis [46, 47]. In this study, we found that clinorotation for 48 h significantly upregulated ER stress markers PERK and ATF6, as well as GRP78 in HUVECs, consistent with a previous study in preosteoblast cells under clinorotation [13].…”
Section: Discussionsupporting
confidence: 91%
“…ER stress and the UPR in ECs can be mediated through the mechanosensitive pathway. Disturbed flow and low magnitude shear stress act through ER stress to promote vascular cell adhesion molecule 1 expression and monocyte adhesion to the endothelium, early events in atherosclerosis [46, 47]. In this study, we found that clinorotation for 48 h significantly upregulated ER stress markers PERK and ATF6, as well as GRP78 in HUVECs, consistent with a previous study in preosteoblast cells under clinorotation [13].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from nonatherosclerotic swine suggested that the ER stress markers IRE1, XBP1, and ATF6 are activated in ECs in atherosclerotic-susceptible areas of the aorta [ 27 ]. Recently, studies have found that disturbed blood flow with low shear stress (SS), a major atherogenic factor leading to EC dysfunction, can directly induce ER stress in ECs, thus exerting critical effects on the progression of atherosclerosis [ 28 ]. For in vitro cultured ECs, atherogenic SS preferentially upregulated the expression of the UPR regulator GRP78 through a p38- and integrin alpha2beta1-dependent mechanism before atheroprone lesion development, which reflects a potential atheroprotective and compensatory response to ER stress [ 29 ].…”
Section: Proatherogenic Effects Of Er Stress In Different Cell Typmentioning
confidence: 99%
“…It is worth noting that these effects can all be ameliorated by ursodeoxycholic acid (UDCA). In a disturbed flow-induced atherosclerosis mouse model, UDCA effectively reduced ER stress, evidenced by decreased expression of XBP1 and CHOP in ECs, and it inhibited the inflammatory response and apoptosis of ECs caused by disturbed flow, thus suppressing the formation of atherosclerotic plaques [ 28 ].…”
Section: Proatherogenic Effects Of Er Stress In Different Cell Typmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress is specified in dyne per cm 2 , in which 1 dyne per cm 2 is 0.1 Pa or 0.1 N per m 2 . We used a unidirectional steady flow (shear stress of 20 dyne/cm 2 ) for LSS and a bidirectional disturbed flow (shear stress of ±5 dyne/cm 2 ) for oscillatory shear stress (OSS), as described previously 17,18 . In the crossover experiment between LSS and OSS, HUVECs were exposed to LSS or OSS for 24 h, followed by exposure to the other type of shear stress for 24 h.…”
Section: Methodsmentioning
confidence: 99%